PENGEMBANGAN VIDEO PEBELAJARAN KIMIA PADA MATERI IKATAN ION SMA KELAS X - Alimah, Alimah; Harun, Andi Ifriany; Sartika, Rody Putra (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2023)
This study aimed to develop learning media in the form of chemistry learning videos and used as a medium to facilitate the study of chemical bonding material. The method used is research and development (Research and Development) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation. The feasibility of this media is seen from the material, media and language feasibility assessment sheets which are validated by three experts in their respective fields The results of the feasibility test of material, media and language respectively obtained an average percentage of 94%, 92.7% and 96% which shows that this chemistry learning video media is very feasible to use.Keywords: Development; media; chemistry learning videos